Measuring Moral Injury: Psychometric Properties of the Moral Injury Events Scale in Two Military Samples. (October 2016) - Bryan, Craig J.; Bryan, AnnaBelle O.; Anestis, Michael D.; Anestis, Joye C.; Green, Bradley A.; Etienne, Neysa; Morrow, Chad E.; Ray-Sannerud, Bobbie
As the construct of moral injury has gained increased conceptual and empirical attention among military personnel and veterans, preliminary attempts to operationalize and measure the construct have emerged. One such measure is the Moral Injury Event Scale (MIES). The aim of the current study was to further evaluate the MIES's psychometric properties in two military samples: a clinical sample of Air Force personnel and a nonclinical sample of Army National Guard personnel. Exploratory and confirmatory factor analyses across both samples supported a three-factor solution: transgressions by others, transgressions by self, and betrayal. Transgressions-Others was most strongly associated with posttraumatic stress; Transgressions-Self was most strongly associated with hopelessness, pessimism, and anger; and Betrayal was most strongly associated with posttraumatic stress and anger. Results support the construct validity of the MIES, although areas for improvement are indicated and discussed.